High-Mobility Group A1 Promotes Cardiac Fibrosis by Upregulating FOXO1 in Fibroblasts - Xie, Qingwen; Yao, Qi; Hu, Tongtong; Cai, Zhulan; Zhao, Jinhua; Yuan, Yuan; Wu, Qing Qing; Tang, Qi-zhu (Frontiers in Cell and Developmental Biology, 2021)
High-mobility group A1(HMGA1), an architectural transcription factor, participates in a number of fundamental cellular processes. However, the implication of HMGA1 in cardiac fibrosis is still unknown. Here we investigated the impact of HMGA1 on cardiac fibrosis. Mice cardiac fibrosis model was constructed via subcutaneous injection of isoproterenol (ISO) or angiotensin II (AngII) infusion. Adult mice cardiac fibroblasts (CFs) were isolated and cultured. CFs were stimulated with transforming growth factor-β1 (TGF-β1) for 24h. As a result, HMGA1 was upregulated in fibrotic hearts as well as TGF-β-stimulated CFs. Overexpression of HMGA1 in CFs aggravated TGF-β1 induced cell activation, proliferation and collagen synthesis. Overexpression of HMGA1 in fibroblasts by adeno-associated virus 9 dilivery system with a periostin promoter accelerated cardiac fibrosis and cardiac dysfunction. Moreover, HMGA1 knockdown in CFs inhibited TGF-β1 induced cell activation, proliferation and collagen synthesis. Mechanismly we found that HMGA1 increased the transcription of FOXO1. FOXO1 inhibitor, AS1842856 counteracted the adverse effects of HMGA1 overexpress in vitro. HMGA1 silence in mice heart could alleviate AngII induced cardiac fibrosis and dysfunction. However, FOXO1 knockdown in mice heart abolished the deteriorated effects of HMGA1 overexpress in mice. Collectively, our data demonstrated that HMGA1 play a critical role in the development of cardiac fibrosis via regulating FOXO1 transcription.